Growth and Productivity of Carrots (Daucus carota) Applied with Bio-Stimulant Solution - Oñal, Jr., Paulino A; Cabillan, Eged B.; de la Paz, Nathaniel Arly A.; Togle, Christian; Andrade, Francis E.; Gayat, Allan G.; Buenafe, Owen B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Carrots (Daucus carota) is an essential vegetable because of its high beta-carotene (Vitamin A). This study seeks to determine the growth and yield performance of carrots applied with different concentrations of bio-stimulant (BSS). This study was conducted at the University of Negros Occidental – Recoletos, School of Agriculture last December 28, 2023 to March 27, 2024. Eighty (80) carrot seeds (Kaneko Bonfire Variety) were used as planting materials. The seedlings were transferred in polyethylene bags using the Complete Randomized Design (CRD) with four treatments replicated four times. The treatments were the Control (no BSS), 10%, 20%, and 30% BSS. The BSS was applied at the plant base 15 and 35 days after transplanting (DAT). The data gathered was analyzed utilizing the STAR 2.1.0 software. To determined the relationships among different characteristics, we used Pearson's Product Moment Correlation Analysis to assess the correlations and associations. The results indicate that plants applied with 30%BSS have an average stem length of 17.79cm, more foliage of 7.95, bigger taproots with 9.28cm, heavier taproots of 32.45gm, heavy stems and leaves at 16.35gm, biomass accumulation of 46.60gm, and average yield of 16,225kg/hectares. The control (0 BSS), on the other hand, has an average stem length of 14.75cm, fewer leaves at 7.10, smaller taproots with 7.59cm, lighter taproots of 16.90gm, the lighter weight of stems and leaves at 10.15gm, smaller biomass acculation of 28.98gm, and lower yields at 8,450kg/hectare. This study recommends the application of 30% bio-stimulant concentration in enhancing the growth and yield performance of the carrot plants.